Association of graft effluent parameters with donor body mass index, graft quality, and post-transplant events - Oweira, Hani; Lahdou, Imad; Daniel, Volker; Schmidt, Jan; Mehrabi, Arianeb; Sadeghi, Mahmoud (Annals of transplantation, 2018)
[b]BACKGROUND[/b] - We evaluated whether effluent parameters prior to reperfusion correlate with post-transplant outcomes in liver transplant recipients. - [b]MATERIAL AND METHODS[/b] - Concentrations of high mobility group box 1 protein (HMGB1), uncleaved cytokeratin-18 (M65), caspase-cleaved cytokeratin 18 fragment (M30), alanine aminotransferase (ALT), aspartate aminotransferase (AST), gamma-glutamyl transpeptidase (GGT), and alkaline phosphatase (ALP) were measured in effluent samples from 53 adult liver recipients (42 survived for 1 year and 11 did not survive). - [b]RESULTS[/b] - Effluent concentrations of ALP (p=0.006), AST (p=0.050), and Ca++ (p=0.003) were higher in patients with bacteriemia in the first post-transplant year and ALP (p=0.015) was higher in patients with early graft dysfunction (EAD). Multivariate analysis of effluent parameters showed that Ca++ >0.30 mmol/l (p=0.012, odds ratio [OR]=7.12, confidence interval [CI]=1.56-32.58), and ALP ≥27 IU/l (p=0.033, OR=5.31, CI=1.14-27.74) were significantly associated with 1-year post-transplant bacteriemia, whereas ALP ≥27 IU/l (p=0.020, OR=5.56, CI=1.32-23.46) was significantly associated with EAD. HMGB1 >54 pg/ml (p=0.008, OR=6.05, CI=1.59-23.00) was significantly associated with the donor body mass index (p=0.008, OR=6.05, CI=1.59-23.00) and fatty liver (p=0.005, OR=11.68, CI=2.10-64.01). - [b]CONCLUSIONS[/b] - Effluent parameters are indicators of liver quality and predict the outcome of liver transplantation. High effluent Ca++ and ALP are risk factors of post-transplant bacteriemia. In addition, high ALP is a risk factor of EAD, and high HMGB1 is an indicator of liver quality.